Visual and real-time imaging focusing for highly sensitive laser-induced fluorescence detection at yoctomole levels in nanocapillaries. Issue 16 (29th January 2020) - Zhang, Wenmei; Liu, Lei; Zhang, Qi; Zhang, Dongtang; Hu, Qin; Wang, Yanan; Wang, Xiayan; Pu, Qiaosheng; Guo, Guangsheng
Abstract : We developed a highly sensitive laser-induced fluorescence detection system, involving visual and real-time imaging focusing instead of the use of fluorescent reagents, for the detection of analytes in nanocapillaries. Abstract : A highly sensitive laser-induced fluorescence detection system with real-time imaging focusing instead of the use of fluorescent reagents were developed for the detection of analytes in nanocapillaries. A cylindrical lens was adopted for the shaping of a laser beam to increase its spatial resolution. The limit of detection with a capillary having a radius of 440 nm was 6.76 yoctomoles (or four molecules) for fluorescein, and 84.5 yoctomoles (or 51 molecules) for FAM-labeled Hsa-miR-17. The designed system exhibited high sensitivity and stability for femtoliters of sample and was hence indicated to be suitable for analyses of single cells.